TLR5 is a new reporter for triple‐negative breast cancer indicated by radioimmunoimaging and fluorescent staining. Issue 12 (1st October 2019) - Shi, Dai; Liu, Weiwei; Zhao, Shanshan; Zhang, Chao; Liang, Ting; Hou, Guihua
Abstract: Triple‐negative breast cancer (TNBC) is a highly aggressive tumour that lacks marker for targeted diagnosis. Recently, it was reported that toll‐like receptor 5 (TLR5) was associated with some kind of tumours, especially in TNBC, but whether it could be used as a non‐invasive monitoring target is not fully understood. Here, we established TLR5 − 4T1 cell line with lentivirus‐shRNA‐TLR5 knock‐down transfection (with tag GFP, green fluorescent protein, TLR5 − 4T1) and control TLR5 + 4T1 cell line with negative control lentivirus transfection. The effect of TLR5 down‐regulation was detected with qPCR and Western blot. 125 I‐anti‐TLR5 mAb and control isotype 125 I‐IgG were prepared and injected to TLR5 +/− 4T1‐bearing mice models, respectively. Whole‐body phosphor‐autoradiography, fluorescence imaging and biodistribution were performed. Furthermore, ex vivo tumour TLR5 expression was proved through immunohistochemistry staining. We found that 125 I‐anti‐TLR5 mAb could bind to TLR5 + 4T1 with high affinity and specificity. Whole‐body phosphor‐autoradiography after 125 I‐anti‐TLR5 mAb injection showed TLR5 + 4T1 tumour images in 24 hours, more clearly in 48 hours. Radioactivities in tumour tissues were positively related with TLR5 expression. Biodistribution assay showed that 125 I‐anti‐TLR5 mAb was mainly metabolized through the liver and kidney, and 125 I‐anti‐TLR5 mAb was much more accumulated in TLR5 + 4T1 tumour than TLR5 − 4T1. In vivo fluorescence imaging successfully showed tumour tissues clearly both in TLR5 + and TLR5 − 4T1 mice compared with lentivirus untreated 4T1 tumour. Immunohistochemistry staining showed that TLR5 expression in tumours was indeed down‐regulated in TLR5 − 4T1 mice. Our results indicated that 125 I‐antiTLR5 mAb was an ideal agent for non‐invasive imaging of TLR5 + tumours; TLR5 may be as a novel molecular target for TNBC non‐invasive diagnosis.